Exploring factors influencing awareness and knowledge of human papillomavirus in Chinese college students: A cross-sectional study - Xian Chen; Ting Xu; Jinfeng Wu; Cuihua Sun; Xue Han; Dan Wang; Zhengxian Zhang; Chengping Qiao; Xiaoxiang Tao (Taylor & Francis Group, 2024)
Cervical cancer remains a significant health burden in China, characterized by high incidence and mortality rates, which are exacerbated by low Human Papillomavirus (HPV) vaccination coverage, leading to substantial loss of productivity, emotional suffering, and family strain. Understanding factors that influence HPV awareness and knowledge is crucial for developing effective educational strategies. This cross-sectional study, conducted from September to October 2022, involved 2,679 college students from various educational institutions in Jiangsu Province, China. Data were collected via an online questionnaire covering demographics, HPV knowledge, and vaccination behaviors. Statistical analyses, including Chi-square tests and multifactorial logistic regression, were used to identify factors influencing HPV knowledge. The study revealed that while over 90% of students correctly identified HPV's transmission and risks, significant knowledge gaps and misconceptions persist, particularly regarding HPV's association with HIV/AIDS and its treatment. Factors significantly associated with better HPV knowledge included age (22-24 years), female gender, being a medical major, being in a relationship, familiarity with HPV, and participation in sexual education programs. Despite a high willingness to receive the HPV vaccine (91.64%), actual vaccination rates remained low. These findings suggest that while Chinese college students were generally aware of HPV, targeted educational interventions are essential to address knowledge gaps and promote HPV vaccination effectively.